Buildup of federal universities' social responsibility in the context of development of Russia's regions. (2018) - Shelomentsev, Andrey; Kozlova, Olga; Antropov, Vladimir; Terentyeva, Tatyana
The paper deals with processes of development of a university's social responsibility in the regional community. The content of ten websites of Russia's federal universities and of official sites of regional authorities of their respective locations was taken as the initial empiric material. Theoretical analysis of basic viewpoints on the nature of buildup of universities' social responsibility was conducted. Basing on the socio-cultural approach to analysis of the mission and lines of the universities' activities, the authors generalised modern practices of social responsibility realisation and gave insight into prospective lines of the universities' activity in the context of the socio-economic development of Russian regions. As a working hypothesis, it has been assumed that it is the human and professional experience of regional leaders that has considerable influence on the formation of universities and regions' mutual social responsibility for realisation of socio-economic objectives of the regional development. Finally, conclusions about horizons and ways of enhancement of the role of social responsibility within the system of interrelations between universities and regions were formulated.